Resolution of an Infection with Leishmania braziliensis Confers Complete Protection to a Subsequent Challenge with Leishmania major in BALB/c Mice - Lima Hermenio C; DeKrey Gregory K; Titus Richard G (Memorias do Instituto Oswaldo Cruz, 1999)
Both Leishmania major and L. braziliensis induce cutaneous leishmaniasis in BALB/c mice. Whereas BALB/c mice die of infection with L. major, they cure an infection with L. braziliensis. We report here that after curing an infection with L. braziliensis, BALB/c mice are resistant to challenge with L. major. When challenged with L. major, L. braziliensis pre-treated BALB/c mice mounted a delayed-type hypersensitivity response to L. major and produced high amounts of interferon-g (IFN-g ) but low amounts of interleukin-4. The IFN-g produced by the L. braziliensis pre-infected mice was involved in the protection seen against L. major challenge since treating the mice with a neutralizing anti-IFN-g abrogated the protection. This suggests that cross-reactive antigen epitopes exist between L. braziliensis and L. major and that pre-infection with L. braziliensis primes BALB/c mice to epitopes on L. major that can elicit a protective Th1 response to the parasite.